The Effect Of Service Quality And Promotion On Purchase Decisions Mediated By Brand Image (Study On Sales Of Wuling Car In Manado) - admin; Tecoalu, Melitina; Wahyoedi, Soegeng (GEMA EKONOMI, 2022)
This study aims to determine the effect of service quality and promotion on purchasing decisions mediated by brand image (Study on Wuling car sales in Manado). The object of research in this study is the quality of service, promotion and purchase decisions and brand image. The subject is Wuling car consumers in Manado. The population in this study were 260 people and the sample was 72 people. The data collection technique in this study was carried out by questionnaires and literature study, while the data analysis technique used tools from the SmartPLS-SEM (Partial Least Square-Structural Equation Modeling) software. For the results obtained in this study indicate that the effect of service quality on purchasing decisions has a significant influence, for the effect of service quality on brand image has a significant influence. The effect of promotion on purchasing decisions has an insignificant effect. The effect of promotion on brand image has an insignificant effect. The influence of brand image on purchasing decisions has a significant influence. The influence of service quality on purchasing decisions mediated by brand image has a significant influence. For the effect of promotion on purchasing decisions mediated by brand image has an insignificant effect.